Discipleship: Seeking the "Kingdom and his righteousness" - Nel, Malan (HTS teologiese studies, 2017)
When membership of the faith community gets separated from Biblical concepts for us Christians the church is gradually and slowly getting into trouble. This is especially true when membership and discipleship are separated. In the first article, I have mentioned that discipleship may have become unpopular because of mainly two reasons: the wrong association with confrontational evangelism and secondly for the inconvenience of the radical nature of discipleship, especially in a situation where churches are still monocultural and still prefer the ‘convenience’ of a culturally constituted and dominated church. In this article, the focus will be on the role of the church in seeking the ‘Kingdom and his righteousness’ (Mt 6:33) and on what seeking might entail, with special reference to continuing formation of the membership on this journey of following the Christ. The background to my research problem and question is that the ‘we’ can just not afford that people, because of the church, not being serious about herself, turn away from the church – but turn to God: ‘Everyday people are straying away from the church and going back to God’ (Lenny Bruce †1966). This is just not normal.